Severe electrolytes disorders with the interstitial kidney alterations in the patient with the history of total thyroidectomy and parathyroidectomy: possible role of vitamin D deficiency. Issue 6 (6th April 2018) - Kawakita, Emi; Kanasaki, Keizo; Hirai, Taro; Tsuda, Shin‐ichi; Watanabe, Ai; Nitta, Kyoko; Kitada, Munehiro; Ogura, Yoshio; Takagaki, Yuta; Fujii, Mizue; Nagai, Takako; Shimada, Keiji; et al.
Key Clinical Message: Vitamin D plays vital role for the health, and its deficiency has been implicated in the diverse pathological conditions such as hypomagnesemia and abnormal immune system. Here, we present a case of severe electrolytes disorders (hypokalemia and hypomagnesemia etc.) and kidney damages associated with vitamin D deficiency. Abstract : Vitamin D plays vital role for the health, and its deficiency has been implicated in the diverse pathological conditions such as hypomagnesemia and abnormal immune system. Here, we present a case of severe electrolyte disorders (hypokalemia and hypomagnesemia etc.) and kidney damages associated with vitamin D deficiency.